Analysis of Sharia Tourism Service Quality Using the CARTER Model - Rachman Mulyandi; Indah Senada Hutabarat; Tirta Jaya Jihanda; Yustinus Saulus (Universitas Bumigora, 2025)
The sharia tourism industry has experienced significant growth in recent years, making service quality a key factor in creating customer satisfaction and loyalty. Currently, there is no service quality dimension specifically designed for sharia tourism, so businesses and regulators still rely on a general framework that is less sensitive to sharia values. This study aims to identify service quality dimensions that can be adapted from other organisations, particularly Islamic banking, by applying the CARTER (Reliability, Assurance, Tangibles, Empathy, Responsiveness) model, which has proven effective in the financial sector. The method used is qualitative, relying on literature analysis techniques of five publi- cations that explicitly integrate the CARTER dimensions in the context of sharia tourism. The analysis shows that combining the five traditional service dimensions with sharia compliance principles produces a holistic unity, namely the CARTER dimensions, which synergistically enhance perceptions of quality, satisfaction, and loyalty among halal tourists. These findings confirm that a cross-sector approach can produce a new framework that is relevant and applicable to the sharia tourism industry. The novelty of this research lies in the revelation that the service quality dimension, which was previously only practised in Islamic banking, can be directly adopted into the halal tourism industry, providing a theoretical and practical basis for the development of service standards, certification, and public policies that target the sustainable improvement of halal market competitiveness.